Chesapeake and Ohio Canal Company memoir - Chesapeake and Ohio Canal Company
Illustrated memoir (119 pages with illustrations) of several months working on the C&O canal. Includes comments on the Maryland countryside, towns, and natural history.
Collection material in English.
Keywords: Canals -- Maryland; Maryland -- Description and travel